2011
DOI: 10.17221/413/2011-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salt stress on physiological response and leaf polyamine content in NERICA rice seedlings

Abstract: NERICA is a new African rice variety, developed by the West African Rice Development Association (WARDA) in 1990s. NERICA rice shows both vigorous growth and tolerance of stressors such as drought and disease. The purpose of this study was to clarify the physiological and biochemical responses to salt stress of NERICA rice seedlings. The degree of growth inhibition caused by salt stress was small in NERICA rice varieties as compared with japonica Nipponbare. Na accumulation in leaf blades was high in salt-sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
1
10
1
Order By: Relevance
“…This observation is consistent with the concept that salt tolerance in NU4 is derived from WAB56–104 as reported previously (Awala et al 2010 ). Interestingly, Yamamoto et al ( 2011 ) reported the similar physiological response of NU3 and NU4 to salt stress compared to other five NU varieties, while NU3 and NU4exhibited different profiles of total amino acids and polyamine. At the same time, Yamamoto et al ( 2011 ) reported salt stress susceptibility of NU2 among the NU varieties.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…This observation is consistent with the concept that salt tolerance in NU4 is derived from WAB56–104 as reported previously (Awala et al 2010 ). Interestingly, Yamamoto et al ( 2011 ) reported the similar physiological response of NU3 and NU4 to salt stress compared to other five NU varieties, while NU3 and NU4exhibited different profiles of total amino acids and polyamine. At the same time, Yamamoto et al ( 2011 ) reported salt stress susceptibility of NU2 among the NU varieties.…”
Section: Resultsmentioning
confidence: 96%
“…Interestingly, Yamamoto et al ( 2011 ) reported the similar physiological response of NU3 and NU4 to salt stress compared to other five NU varieties, while NU3 and NU4exhibited different profiles of total amino acids and polyamine. At the same time, Yamamoto et al ( 2011 ) reported salt stress susceptibility of NU2 among the NU varieties. Those differences of NU varieties in salt stress response imply that multiple genetic components for salt stress adaptation are combined differently in their genomes.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Under salinity stress, an ion imbalance, such as the accumulation of Na + , directly reduces carbon fixation and biomass production in plants. Additionally, K + can counteract Na + stress; thus, the potential of plants to tolerate salinity is dependent on their K + nutrition (Cha‐Um, Supaibulwattana, & Kirdmanee, ; Chen et al, ; Fakhrfeshani, Shahriari‐Ahmadi, Niazi, Moshtaghi, & Zare‐Mehrjerdi, ; Hoang et al, ; Yamamoto, Sawada, Shim, Usui, & Fujihara, ). For this reason, membrane integrity, Na + and K + concentrations, and the ratio between Na + and K + are key parameters that differentiate sensitive and tolerant rice cultivars during salinity stress (Hoang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The application of ZnSO 4 and BAZ-coated urea remarkably lowered the activity of antioxidant enzymes, particularly under salinity stress. The accumulation of harmful Na might have replaced essential nutrients with functions, e.g., the replacement of K and Ca with Na altered stomatal opening and closing, and caused membrane disruption [ 46 , 47 ]. Zinc sulfate and BAZ-coated urea provided relief and lowered the antioxidant enzyme activity, which may be associated with enhancement of the nutrient uptake at the cost of Na accumulation in the plant [ 25 ].…”
Section: Discussionmentioning
confidence: 99%